Dynamic mechanical behavior of prismatic lithium‐ion battery upon impact - Chen, Xiaoping; Wang, Tao; Zhang, Yu; Ji, Hongbo; Ji, Yingping; Yuan, Quan (International journal of energy research, 2019)
Summary Dynamic impact safety of lithium‐ion batteries (LIBs) is a hot subject. The mechanical‐electrical behavior of LIBs under dynamic loading was studied in this study. Drop‐weight tests of two types of indenter, namely, round and flat heads, were conducted. Strain rate and state of charge (SOC) effects on the mechanical properties of LIBs under different indenters were fully discussed. The interaction between mechanical performance and electrical behavior was studied. Experiments show that the structural stiffness of batteries increases with strain rate increase but exhibits little effect from SOC. Different indenters have a significant influence on the mechanical behavior of the prismatic LIBs. Under the same impact rate and SOC, the peak load of a flat head is considerably larger than that of a round head. The battery exhibits a hard short‐circuit under the impact of a round head and a soft short‐circuit under the impact of a flat head. This result shows that the larger the contact area between the indenter and the battery is, the larger the impact load under the same drop‐weight and impact rate will be, although the impact safety of the battery does not decrease. The results provide useful insights into the basic understanding of the electromechanical coupling integrity of LIBs. The effects of SOC and strain rate on the mechanical properties of LIBs were studied under different indenters. The mechanism behavior of drop‐weight impact under two types of indenters was analyzed. Three typical failure modes of batteries under dynamic load were observed and summarized.